Kanthi medallion featuring Lord Agni - Mumbai Archive Project Team (Jio Institute, 2024)
The kanthi medallion features Agni, the Hindu God of fire. The kanthi is a multi-layer necklace made of linked chains, often featuring deities or other cultural motifs on circular medallions.